The Determinants of Personal Solid Waste Management Behaviour of Colombo District Residents - Colombage, V (NSBM Green University, 2018)
Current study focus on proposing a model to capture personal solid waste management behavior of Colombo District consumers in Sri Lanka. The model was developed based on the theory of planned behavior proposed by Ajzen (1991) and the solid waste management hierarchy (SWMH) model proposed by McAllister, (2015). The study will elucidate on a ground level practical approach to solve solid waste management issue in Sri Lanka.
Keywords: individual; solid waste management; social norms; personal norms; situational factors; satisfaction